A Comprehensive Review On Ionic Polymer Metal Composite Applications. Issue 1 (28th March 2016) - ul Haq, Mazhar; Gang, Zhao
Abstract : In this paper, we present a comprehensive review of ionic polymer metal composites (IPMCs) covering their fundamentals, fabrication processes, characterisation and applications. IPMCs are becoming increasingly popular among scholars, engineers and scientists due to their inherent properties of low activation voltage, large bending strain, i.e., transformation of electrical energy to mechanical energy, and properties to be used as bidirectional material, i.e., they can be used as actuators and sensors. Among the diversity of electro active polymers, recently developed ionic polymer metal composites are good candidates for use in bio-related applications because of their biocompatibility. The applications of IPMCs have been growing due to the progression in their manufacturing techniques, development of more accurate control models, and the recently demonstrated sophisticated IPMC actuator applications. This indicates that IPMC actuators hold potential for more sophisticated applications in control. Several recently reported IPMC fabrication processes, their mechanical characteristics and performance, and a number of recent IPMC applications have been reported in this paper. Extensive references are provided for more in-depth explanation.